Evaluation of disk plough combined with rotary blades on some soil physical properties. - Ali, H.; Ahmad, Desa; Othman, Jamarei; Sulaiman, Shamsuddin (2012)
A disc plough combined with rotary blades, defined as Combo plow, used for land preparation for planting has been developed and evaluated at University Putra Malaysia (UPM) Research Farm in the year 2010/2011. The new apparatus includes seven units: chassis, three point hitch, concave disc, transmission systems, rear wheel,rotary blades and rotary blades cover. A multiple tillage operation is reduced to a single path resulting in a reduction of soil compaction, labour, fuel cost and operation time. The objective of the study was to experimentally evaluate the effects of newly developed disc plough combined with rotary blades on bulk density and mean weight diameter. Regression analysis revealed that the bulk density was affected by tillage implements and generally decreased after tillage operation. The mean values of mean weight diameter < 100mm of soil aggregates for the straight type blade at 130 rpm was highest and for the L-shaped was lowest than other rotational speeds'